People Analytics: Exploring the Debates, Drivers, and Performance Impact - McCartney, Steven (Trinity College Dublin. School of Business. Discipline of Business & Administrative Studies, 2021)
People analytics has recently become an emerging trend within the field of HRM. Despite the significant growth of people analytics, many questions around people analytics and its performance impact remain unanswered. Drawing on the resource-based view of the firm (RBV, Barney, 1991), evidence-based management (EBM, Rousseau & Barends, 2011), and strategic human capital theory (Becker, 1964), this dissertation seeks to make an original contribution to knowledge by answering the following research questions: (1) What debates and challenges are emerging as a result of people analytics adoption? (2) What factors contribute to the success of people analytics? (3) How does people analytics impact organizational performance? To do so, the dissertation is organized into three studies, each with its own set of research aims and objectives that logically interconnect to the overarching research questions. In particular, Study 1 presents a systematic literature review addressing the debates and challenges emerging as a result of people analytics adoption. Study 2 aims to address the key knowledge, skills, abilities, and other characteristics (KSAOs) required by HR Analysts through investigating the relationship between analytical and storytelling skills and their impact on individual and team people analytics performance. Finally, Study 3 seeks to understand why, how, and when analytics influence organizational performance. A survey methodology was adopted for Studies 2 and 3. Overall, the dissertation reveals the current debates and challenges in people analytics and finds strong support for the performance impact of people analytics. This research extends our understanding of people analytics by offering new and original contributions to this field. Similarly, it builds theoretical foundations for the impact of people analytics.
APPROVED
Keywords: People Analytics; Strategic Human Capital; Human Capital Resources; Evidence-Based Management